A detailed record of early solar system melting in the carbonaceous achondrites Northwest Africa 7680 and 6962. (18th August 2022) - Hyde, Brendt C.; Moser, Desmond E.; Tait, Kimberly T.; Darling, James R.; Yin, Qing‐Zhu; Sanborn, Matthew E.; Banerjee, Neil R.; Ali, Arshad; Jabeen, Iffat; Moreira, Hugo
Abstract: Detailed textural and geochemical analyses of the carbonaceous achondrites Northwest Africa (NWA) 7680 and NWA 6962 support a rapid progression of thermal events, by similar processes, on the same parent body. The achondrites have olivine compositions of Fa44.8 and Fa47.4 for NWA 7680 and NWA 6962, respectively. Replicate oxygen isotope analyses of grains and bulk powders from NWA 7680 yielded average Δ 17 O values of −1.04 ± 0.03‰ and −1.00 ± 0.05‰, respectively, which is identical to that reported for NWA 6962. The whole rock ɛ 54 Cr compositions are also equivalent for NWA 7680 and NWA 6962 (1.36 ± 0.05 and 1.30 ± 0.05, respectively). Both meteorites are plagioclase‐rich, and NWA 7680 is also Fe‐metal‐rich, suggesting they both formed via differentiation processes that resulted in the pooling of partial melt products. Major element geochemical trends show that both rocks could be formed through the melting of chondritic material on a CR chondrite‐like parent body. This is consistent with oxygen isotope and chromium isotope compositions. Intrusion of a late‐stage melt is evident in both meteorites and the crystallization products include silica‐rich, alkali‐deficient nepheline. The late‐stage liquid has partially melted and mixed with primary plagioclase in NWA 6962. In contrast, the late‐stage liquid was often restricted to grain boundaries in NWA 7680, leaving some of the primary plagioclase crystals intact. In situ dating of NWA 7680 phosphate minerals (merrillite and fluorapatite) reveals that it has not experienced long duration thermal metamorphism, or impact‐related Pb loss and age resetting since 4578 ± 17 Ma ( 207 Pb/ 206 Pb age ± 2σ, within error of solar system age). Phosphates associated with the late‐stage melt in NWA 6962 yield a 207 Pb/ 206 Pb age of 4556.6 ± 8.0 Ma (2σ) within 2σ of the NWA 7680 age. These early dates indicate that the observed chromium isotope signatures in these meteorites were not introduced by a later high‐temperature event, such as late impact accretion processes. These data are consistent with a rapid separation of inner and outer solar system chemical reservoirs, planetesimal melting, differentiation, and cooling, all within several million years of calcium‐aluminum‐rich inclusion formation.